The Mitchells : five for victory - Van Stockum, Hilda, 1908-2006. (Warsaw, N.D. : Bethlehem Books : Ignatius Press, 1995)
Follows the adventures of the five Mitchell children living with their mother and grandmother in Washington D.C. while their father is away fighting in World War II.
Sequel: Canadian summer.
Keywords: Siblings -- Fiction; Family life -- Fiction; World War, 1939-1945 -- United States -- Fiction